Essential oil in roots of Vetiveria zizanioides (L.) Nash ex Small from Bangladesh (Bangladesh Journal of Botany, 2008)
Essential oil from roots of Vetiveria zizanioides (L.) Nash ex Small from Bangladesh was examined by gas chromatography mass spectrometry (GC-MS). Fourteen compounds were identified in root oil. The compositions of oil varied qualitatively and quantitatively. Key words: Vetiveria zizanioides, GC-MS analysis, Essential oil doi:10.3329/bjb.v37i2.1736 Bangladesh J. Bot. 37(2): 213-215, 2008 (December)